Analysis of Traditional Medical Imaging Methods and their Comparison with Ultra-Weak Magnetic Field Imaging - Wenhao Li (International Journal of Public Health and Medical Research, 2026)
Human structural imaging methods such as Computed Tomography (CT) and Magnetic Resonance Imaging (MRI) are essential to modern clinical medicine. These non-invasive tools allow doctors to clearly observe hidden internal organs, bones, and soft tissues, greatly improving diagnosis rate and survival rate. Detailed structural scans also support personalized treatment: surgeons use reconstructed images to plan precise surgery and avoid damaging vital tissues, while radiotherapists pinpoint lesions and limit damage to healthy areas. Serial image comparison can objectively track the development of the disease and treatment results, so that the plan can be adjusted in time. Ultra-weak magnetic field imaging is an emerging medical functional information imaging method. It detects the magnetic field of human body through shielding the earth’s magnetic field. The magnetic field of human organs is extremely weak, so the quality requirements for ultra-weak magnetic medical equipment are extremely high. This paper introduces the applicability and other aspects of ultra-weak magnetic field imaging, highlighting its advantages over traditional medical imaging methods. Finally, the future development prospect of ultra-weak magnetic field imaging is proposed and its importance in safeguarding human health is emphasized.